Effect of at-home and in-office bleaching on microleakage of class V composite resin restorations using different types of universal adhesives: An in vitro study - Mehdi Abed Kahnamouei; Soodabeh Kimyai; Katayoun Katebi; Mohammad Esmaeel Ebrahimi Chaharom; Mehdi Daneshpooy; Mahmoud Bahari; Mahshid Moradi (Tabriz University of Medical Sciences, 2023)
Background. When bleaching agents contact dental structures, they act on restorative materials and adhesive interfaces. This study investigated the effect of "at-home" and "in-office" bleaching on the microleakage of composite resin restorations performed with different universal adhesives in self-etch and etch-and-rinse modes. Methods. Class V cavities were prepared in 132 premolars. The samples were divided into four groups (n=33). All Bond Universal adhesive was used in the first and second groups, and G-Premio Bond adhesive was used in the third and fourth groups. The total-etch mode was used in the first and third groups, and the self-etch mode was used in the second and fourth groups. The samples were divided into three subgroups (n=11). In the first subgroup, home bleaching was used, and in the second subgroup, office bleaching was used. In the third subgroup, bleaching was not performed. The specimens were examined under a stereomicroscope for microleakage. Ordinal regression analysis was applied (P<0.05). Results. The adhesive type, application method, and margin type significantly affected microleakage (P<0.05). The amount of microleakage in All Bond Universal adhesive was significantly higher than in G-Premio Bond adhesive. The chance of microleakage in the self-etch mode was almost twice as high as in the etch-and-rinse mode. The bleaching method did not significantly affect microleakage (P>0.05). Conclusion. Based on the results of the microleakage test, bleaching after composite resin restorations did not significantly affect the microleakage of Class V restorations.